PENGARUH PERILAKU REGRESI PADA INTERAKSI SOSIAL LANJUT USIA DI PANTI PELAYANAN SOSIAL LANJUT USIA BOJONGBATA PEMALANG - Kodaruddin, Wina Nurdini; Apsari, Nurliana Cipta; Raharjo, Santoso Tri (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
Behavior regression is part of the human self-defense mechanism. Aging, decreased productivity and decline in the elderly and lack of self-acceptance can make elderly people feel alienated and feeling stressed. Because of these conditions, the elderly can increasingly refuse to communicate with others and sometimes behaviors such as children or regression behaviors appear. Based on the research that has been done, in the elderly who live in social care institutions, the emergence of this regression behavior affects the pattern of social interaction with other people both with fellow elderly beneficiaries and with caregivers or mentors at the Home. Regression behavior that is raised with frequent intensity can make fellow residents or officers keep a distance to interact and cause disputes between residents of the institution who can later disrupt the institution's conduciveness.